Antioxidant activity, stability, in vitro digestion and cytotoxicity of two dietary polyphenols co-loaded by β-lactoglobulin. (1st March 2022) - Ren, Yongfang; Liu, He; Wang, Danfeng; Liu, Tingting; Zhang, Ruiyan; Wu, Yushu; Zhang, Yongfang; Han, Jun; Liu, Min
Graphical abstract: Highlights: Procyanidin B2 and dihydromyricetin were co-loaded by β-lactoglobulin. PB2 and DMY had synergistic antioxidant activity and cytotoxicity. PB2 and DMY competitively bound to the surface cleft of β-LG. β-LG affected the antioxidant capacity, stability, in vitro digestion and cytotoxicity. Abstract: The combination of multiple dietary polyphenols may have synergistic beneficial effects. And the beneficial effects can be further improved by the encapsulation of proteins. The interactions of procyanidin B2 (PB2) and/or dihydromyricetin (DMY) with β-lactoglobulin (β-LG) were investigated using multi-spectroscopic techniques and molecular docking. The structural change of β-LG in the presence of PB2 and/or DMY was demonstrated by dynamic light scattering, Fourier transform infrared spectroscopy and circular dichroism spectroscopy. Response surface analysis was used to optimize the synergistic antioxidant activity between PB2 and DMY. Besides, the antioxidant activity, stability, in vitro digestion and cytotoxicity of PB2 and DMY in the binary and ternary systems were investigated. These studies will elucidate the interaction mechanism of PB2 and/or DMY with β-LG. The research results can provide theoretical support for the development of functional foods and beverages with synergistic activity, improved stability and bioaccessibility, thereby promoting human health and preventing diseases.